Understanding Profit from the Perspective of Women Daily Cake Sellers - Masradin, Masradin; Potton, Zainal; Syarifuddin, Syarifuddin; Said, Darwis (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
This study aims to uncover the meaning of profit from the perspective of home-based cake sellers in Rappocini District, Makassar, as household-based micro-enterprises who play dual roles in the family economy. Using an interpretive phenomenological approach and The Cultural Shaping of Accounting framework, this study explores how life experiences, cultural values, and domestic conditions shape the meaning of profit beyond formal accounting concepts. Data were collected through in-depth interviews, participant observation, and documentation, then analyzed using NVivo 12. The results of the study revealed five main themes of profit meaning, namely: as a means of fulfilling daily food needs, financing children's education, household needs, savings to face uncertainty, and as working capital for business sustainability. These findings indicate that profit is understood as a source of welfare, security, and family stability and links the household economy and business economy. This study contributes to the development of accounting studies with a cultural and gender perspective, and provides implications for mentoring MSMEs in the social behavior of micro enterprises.